2019
DOI: 10.1186/s40345-019-0148-x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated inflammatory response of monocyte-derived macrophage from patients with BD: a preliminary report

Abstract: Background Innate immune system dysfunction has been recognized as an important element in the pathophysiology of bipolar disorder (BD). We aimed to investigate whether there are differences in the response of macrophages derived from patients in the early stages and late stages of BD and healthy subjects. Methods Human monocytes purified from peripheral blood mononuclear cells (PBMCs) of patients with BD type I (n = 18)—further classified into early- and late stage BD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 62 publications
0
22
1
4
Order By: Relevance
“…It is important to note that these cells were not stimulated, so their results only provide insight as to their behavior at rest. A recent study by Ascoli et al (2019) found that inflammatory macrophage responses after M1/M2 skewing diminished with disease progression in BD, where "early stage" BD macrophages more closely resembled HC macrophage responses, but in later-stage disease the responses were attenuated. Our patients were not considered chronically ill, all were within a year of first symptoms and our findings that macrophages in the AFF group respond similarly to HC after LPS and M1 stimulation supports this research.…”
Section: Discussionmentioning
confidence: 95%
“…It is important to note that these cells were not stimulated, so their results only provide insight as to their behavior at rest. A recent study by Ascoli et al (2019) found that inflammatory macrophage responses after M1/M2 skewing diminished with disease progression in BD, where "early stage" BD macrophages more closely resembled HC macrophage responses, but in later-stage disease the responses were attenuated. Our patients were not considered chronically ill, all were within a year of first symptoms and our findings that macrophages in the AFF group respond similarly to HC after LPS and M1 stimulation supports this research.…”
Section: Discussionmentioning
confidence: 95%
“…The identified flaw in the control of immune system functioning might be connected to the involvement of so many bodily systems with the advancement of the diathesis in BD. 36 A meta-analytic review investigated the likelihood of determining a biomarker signature of illness phase in BD. In the analysis, 53 studies comprising 2467 cases and 2360 controls were included and it showed that in BD hs-CRP, IL-6, BDNF, TNF-α, and soluble TNF-α receptor 1 could discriminate a distinctive affective exacerbation.…”
Section: Inflammatory Biomarkersmentioning
confidence: 99%
“…В настоящее время БАР рассматривают как мультисистемное заболевание, так как оно часто ассоциируется с коморбидными системными воспалительными заболеваниями, такими как сердечно-сосудистые заболевания, абдоминальное ожирение, инсулинорезистентность, аутоиммунные расстройства, которые, как показано, ассоциированы с ранними проявлениями этого заболевания [45][46][47][48]. Существует большое количество исследований, свидетельствующих о дисфункции иммунного ответа, вовлеченного в патогенез БАР [8, 48,49], а именно, сообщается, что БАР сопровождается провоспалительной активацией иммунитета. При этом для депрессии характерна повышенная активность ряда провоспалительных цитокинов, в частности IL-1b, IL-6, TNF-[7, 24, 50-52], а также растворимых рецепторов к ним [52].…”
Section: моноциты и барunclassified
“…Было высказано предположение, что воспаление, включающее изменения уровней воспалительных цитокинов, кортикостероидов, активности окислительного стресса и изменение нейрогенеза, является одной из причин, способной объяснить некоторые клинические особенности БАР [50], которые, по мнению авторов, включают прогрессирующее укорочение интервалов между эпизодами с каждым новым рецидивом заболевания. Действительно, по сообщениям некоторых авторов, увеличение продолжительности болезни и количества маниакальных и депрессивных эпизодов повышают риск развития соматических сопутствующих заболеваний, особенно связанных с метаболической и иммунной дисфункцией, при этом депрессия связана с риском развития, например сердечно-сосудистых заболеваний, инсульта, диабета и ожирения [48]. Было показано, что повышенная секреция цитокинов IL-1 , TNF-, IL-6 у больных БАР по сравнению со здоровыми людьми выявлялась на ранних стадиях болезни [22], тогда как по мере прогрессирования заболевания секреция цитокинов значительно снижалась [48].…”
Section: моноциты и барunclassified